Analisis Kesesuaian Desain Perumahan terhadap Karakteristik Tanah dan Potensi Risiko Geoteknik di Aceh Besar - Zikrina Melinda; Asrul Sidiq (Prodi Arsitektur, Fakultas Sains dan Teknologi bekerja sama dengan Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
The rapid development of commercial housing often overlooks local geotechnical characteristics, particularly in areas dominated by soft soils. This study aims to evaluate the suitability of commercial housing design typologies in terms of engineering geological characteristics in Lamkeneung, Aceh Besar, Indonesia. A descriptive-quantitative approach with an evaluative method was employed using primary data from Detailed Engineering Design (DED) documents and secondary data from engineering geological maps and relevant literature. The evaluation was conducted on three housing types, namely Type 36, Type 52, and Type 70, based on six assessment parameters